Climate Change and Gender Based Violence: Overview of Current Research - Garance, Garance; Huyer, Sophia; Seager, Joni (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
UN Women has identified violence against women and girls (VAWG) and climate change as the two most pressing global emergencies and sustainable development challenges. “With devastating social, cultural, economic, health and human rights impacts, affecting women and girls disproportionately, especially the most marginalized groups” (UN Women and IUCN, 2022, 1), climate change presents threats to global sustainability (UN Women and IUCN, 2022; Turquet et al, 2023).